Human Capital Strategic: Organization Commitment, Training Need Analysis, Development People, Individual Development Plan, and Performance Appraisal - Wenny Desty Febrian; Anggia Rettrisunz Pim Panjaitan; Kamsariaty; Josua Panatap Soehaditama; Supardi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this manuscript is to search the literature to support the variables of this manuscript and to provide results for consideration in future studies as a research gap or alongside other research items this study is to see the effectiveness of the human capital management department, where in general human capital will have several approaches to maintaining its assets, namely the human resources working in the company. The novelty of this mini literature review is the existence of a research model framework that has never existed or was formed before. In this article, a literature review of several international articles that are relevant to the variable being studied is carried out. The results show that there are several variables that are significant the implications of this article must be carried out in-depth such as through interviews with informants to confirm the literature review